Content Kebijakan dalam Implementasi Peraturan Daerah untuk Pengurangan Kematian Bayi di Kabupaten Kupang - Rene, Mariayani Oktafiana; Kismartini, Kismartini; Purnaweni, Hartuti (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2019)
The content of a policy is one of the factors that determine success in the policy implementation process. This study aims to analyze how the content of Regional Regulation (Perda) No. 3 of 2016 as a policy for reducing infant mortality in Kupang regency, using one of the elements of the implementation model by Najam (1995), namely content. The method used is qualitative with data collection techniques in the form of observation, interviews and literature studies. The results of the study show that the content of Regional Regulation (Perda) No. 3 of 2016 clearly contain the objectives to be achieved, and how to achieve these objectives. The way to achieve the stated goals is also in accordance with the causes of infant mortality problems in Kupang Regency